The Socio-spatial Configuration of Muslims in Lisbon - McGarrigle, Jennifer (2020)
This chapter explores various elements of the religious spatiality of Muslims in Lisbon. I conduct a spatial analysis of religious landscapes, conceived as residence and collective spatial appropriation for worship, for the metropolitan area. Processes underlying patterns of local emplacement are explored using qualitative data from interviews with 21 religious leaders. I show that the Portuguese Muslim Community can be best understood in the context of sub-collective Muslim groups that are represented in multiple spaces across the city that reproduce differences in denomination, nationality, ethnicity, language and even socio-economic status. The configuration of the Islamic community in micro-clusters with diverse places of worship helps preserve and transmit ethno-cultural practices yet, simultaneously, reduce visibility at the city level. Local community development reaches beyond religion to include cultural and, at times, social provision, thus, playing a role in transforming local dynamics and in generating social capital.